2022
DOI: 10.1186/s12909-022-03836-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect analysis of a virtual simulation experimental platform in teaching pulpotomy

Abstract: Background The experimental teaching of pediatric dentistry is a bridge between theoretical study and clinical practice, and virtual simulation technology provides a new method of instruction. Methods We built an experimental teaching platform using virtual simulation technology for vital pulpotomy that includes learning and examination modes. A total of 199 students majoring in stomatology in the fourth year at Sun Yat-Sen University were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…By replacing part of classroom teaching with virtual simulation experiment teaching, the number of experimental animals can be reduced. By combining virtual simulation experiment teaching with classroom teaching, the effectiveness of experimental teaching can be improved [13][14][15]. Lo et al stated that "despite the appetite for virtual and augmented reality models, empirical evidence supporting current technologies is limited" [3].…”
Section: Alternative Methods To Animal Experimentationmentioning
confidence: 99%
“…By replacing part of classroom teaching with virtual simulation experiment teaching, the number of experimental animals can be reduced. By combining virtual simulation experiment teaching with classroom teaching, the effectiveness of experimental teaching can be improved [13][14][15]. Lo et al stated that "despite the appetite for virtual and augmented reality models, empirical evidence supporting current technologies is limited" [3].…”
Section: Alternative Methods To Animal Experimentationmentioning
confidence: 99%
“…The virtual simulation-based educational approach is an emerging interactive pedagogical strategy using computer-generated virtual simulation technology that immerses learners in a setting with real-world sensory perceptions and allows a series of practices and feedback in this digital world [ 1 ]. The utilization of virtual simulation in experimental teaching has become increasingly prevalent and is considered a significant reform in higher education [ 2 , 3 ], which emerges from the integration of cutting-edge virtual simulation technology and a paradigm shift towards student-centered learning [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aphorism of training of the surgeon proposed by Halsted in 1904 that ‘see one, do one, teach one’ is being transformed into ‘see one, repeat virtual stimulation, real practice’ [ 13 ]. Meanwhile, the visualization and interactive experimental procedure largely stimulated the learners’ study motivation and initiative [ 3 , 14 ]. A wide array of studies also confirmed the benefits of virtual stimulation-based medical training in skills development and patient safety [ 15–18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Live pulp treatment or pulpotomy aims to preserve pulp life and stimulate the remaining pulp to repair the structural and functional pulp-dentin complex (5). It means that the tooth pulp survives and regenerates the dentin in the exposure area to cut off the body's internal environment from the oral cavity by creating a biological barrier and preventing the re-invasion of pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients may not be present at any of the follow-up times. Therefore their data will not be available to researchers at the relevant follow-up times, which have occurred in the National Vital Pulp Therapy Project and can be interpreted in terms of results (5). The result has no side effects.…”
Section: Introductionmentioning
confidence: 99%